Pelaksanaan Rencana Kerja Operasional (RKO) Program Posyandu Lansia Sehati Wilayah Kerja Puskesmas Wonorejo Samarinda - Rindha Mareta Kusumawati; I Putu Sukra; Avita Yulianti Harahap (FORIKES, 2020)
Sehati Integrated Health Service Center (Posyandu) is one of four Integrated Health Service Center (Posyandu) for the Elderly at the Wonorejo Health Center. During this time, the Integrated Health Service Center (Posyandu) for the Elderly has not been maximized because of inadequate human resources. This study aims to describe the implementation of the operational work plan in Sehati Integrated Health Service Center for Elderly programs in Wonorejo Health Center works area. The type of research was qualitative with a phenomenological approach. The research informants were the chief of the Health Center, senior program person in charge and cadres. Observation, interviews, and documentation are used to collect the data. The techniques to analyze data were data collection, reduction, data presentation, and verification. The results showed that there was no background for the role of the PKK due to the lack of human resources however the person in charge was right and supporting resources namely equipment for the Integrated Health Service Center for Elderly activities were available. There had been no role of the PKK due to lack of human resources, cadres were still less active and there were still elderly people who didn’t come to the Integrated Health Service Center due to lack of motivation from the elderly family are the Conclusion of this research. The person in charge of the implementation of the Integrated Health Service Center for the elderly was appropriate namely the chief of RT and the leader of the Integrated Health Service Center for the elderly cadres. Supporting resources such as the equipment for the activities of the Integrated Health Service Center for the elderly programs are already available at the moment. Keywords: posyandu; elderly; cadres ABSTRAK Puskesmas Wonorejo memiliki 4 Posyandu Lansia, salah satunya adalah Posyandu Sehati. Pelaksanaan Posyandu lansia belum maksimal karena SDM kurang memadai. Penelitian ini bertujuan untuk menggambarkan pelaksanaan rencana kerja operasional program posyandu lansia sehati wilayah kerja Puskesmas Wonorejo Samarinda. Jenis penelitian adalah kualitatif dengan pendekatan fenomenologi. Informan penelitian adalah kepala puskesmas, pemegang program lansia dan kader. Teknik pengumpulan data melalui observasi, wawancara dan dokumentasi. Teknik analisis data yaitu pengumpulan data, reduksi, penyajian data dan verfikasi. Hasil penelitian yaitu latar belakang belum ada peran dari PKK dikarenakan kurangnya SDM, penanggung jawab sudah tepat dan sumber daya pendukung yaitu peralatan untuk kegiatan posyandu lansia sudah tersedia. Kesimpulan belum ada peran dari PKK dikarenakan kurangnya SDM, kader masih kurang aktif dan masih ada lansia yang tidak datang ke posyandu karena kurangnya motivasi dari keluarga lansia tersebut. Penanggung jawab pelaksanaan posyandu lansia sudah tepat yaitu ketua RT dan ketua kader posyandu lansia. Sumber daya pendukung, yaitu peralatan kegiatan program posyandu lansia sehati sudah tersedia. Kata kunci: posyandu; lansia; kader